Alteration in the number, morphology, function, and metabolism of erythrocytes in high-altitude polycythemia - Yu, Song; Ye, Yi; Wuren, Tana; Yi, Hai (Frontiers in Physiology, 2024)
Introduction: High-altitude polycythemia (HAPC) is a common chronic high-altitude disease characterized by significantly increased erythrocyte, hemoglobin (Hb), and hematocrit values and decreased arterial oxygen saturation. The mechanisms underlying HAPC development are unclear;we aimed to investigate this in an HAPC rat model. Methods:Twelve Sprague-Dawley rats were divided into control and HAPC groups. The HAPC group was exposed to hypobaric hypoxia. Bone marrow, peripheral blood reticulocytes (RETs), and peripheral blood erythrocyte apoptosis were measured using flow cytometry. Erythrocyte osmotic fragility (EOF) tests were conducted. Abnormal erythrocytes were counted using electron microscopy. Plasma-free hemoglobin, 5′-nucleotidase (CD73), adenosine, erythrocyte cytosolic adenosine, sphingosine-1phosphate (S1P), and 2,3-bisphosphoglycerate (BPG) levels were measured using enzyme-linked immunosorbent assays. Erythrocyte metabolic pathway-related protein (adenosine A2B receptor [ADORA2B], erythrocyte equilibrative nucleoside transporter 1 [eENT1], sphingosine kinase 1 [SPHK1], phospho-SPHK1, bisphosphoglycerate mutase [BPGM], and glyceraldehyde 3-phosphate dehydrogenase [GAPDH]) levels were assessed by western blotting. Results: The HAPC rat model was successfully established (Hb >210 g/L). Indices of bone marrow and peripheral blood RET proportions were significantly higher in the HAPC than the control group (P = 0.04 and P < 0.001, respectively). The proportion of peripheral blood erythrocytes in early apoptosis was significantly lower in the HAPC than the control group (P < 0.001). Vesicular erythrocyte and acanthocyte proportions were significantly higher in the HAPC than the control group (P < 0.001 and P = 0.019, respectively). The EOF tests revealed that 50% erythrocyte hemolysis occurred at 4.0-4.5 and 4.5-5.0 g/L NaCl in the control and HAPC groups, respectively. Plasma-free hemoglobin, CD73, adenosine, erythrocyte cytosolic adenosine, S1P, and 2,3-BPG levels and ADORA2B, eENT1, phospho-SPHK1, S1P, BPGM, and GAPDH erythrocyte expression levels (all P ≤ 0.02) were significantly higher in the HAPC than the control group. Conclusions:In model rats, an HAPC-related erythrocyte increase was associated with enhanced bone marrow hematopoietic function and reduced erythrocyte apoptosis, whereas numerous abnormal erythrocytes, increased EOF, and reduced hemolysis resistance were associated with erythrocyte metabolism. CD73/adenosine/S1P/2,3-BPG and eENT1/adenosine/BPGM/2,3-BPG metabolic pathways in erythrocytes were activated in HAPC rats, facilitating oxygen release. These findings further reveal the intrinsic HAPC mechanism.